2017
DOI: 10.1039/c7ra06857c
|View full text |Cite
|
Sign up to set email alerts
|

4,6-Dimethyl-2-mercaptopyrimidine as a potential leveler for microvia filling with electroplating copper

Abstract: Filling performance of microvia was defined as following equation: η = (A/B) × 100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…According to previous research, high electron density regions (e. g., N=N of JGB) have strong coordination and adsorption capability to the copper surface. [13] This region could offer electrons to the lowenergy empty molecular orbitals of copper to form a coordinate/covalent bond, [15,52] which indicated that the carbonyl region of 1 e was the probable adsorption site for the adsorption of 1 e on the copper surface.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous research, high electron density regions (e. g., N=N of JGB) have strong coordination and adsorption capability to the copper surface. [13] This region could offer electrons to the lowenergy empty molecular orbitals of copper to form a coordinate/covalent bond, [15,52] which indicated that the carbonyl region of 1 e was the probable adsorption site for the adsorption of 1 e on the copper surface.…”
Section: Resultsmentioning
confidence: 99%
“…The sidewalls of these holes were metalized by electroless copper after plasma treatment. Following that, the pretreatment techniques and electroplating procedures have been presented in detail elsewhere . Test boards were plated at a current density of 2.00 A dm −2 for 60 min at 25 °C in a haring cell with a 1.5 L working volume.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18] Small molecule levelers with these characteristics, such as 4-amino-2,1,3-benzothiadiazole and 4,6-dimethyl-2mercaptopyrimidine (DMP), have appeared in previous reports. 19,20 However, they are still in the preliminary research phase and the mechanism of adsorption still remains unclear.…”
Section: Introductionmentioning
confidence: 99%